On the Stability of the Basic East-West Velocity Flow - Camerlengo, Alejandro Livio (Universiti Putra Malaysia Press, 1999)
Instability due to the horizontal shear of the basic state velocity, V, is addressed. It is corroborated that instability happens whenever a2 VI of co variates negatively with V.